2010
DOI: 10.5101/nbe.v2i4.p236-244
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CdSe/ZnS quantum dots covered multi-walled carbon nanotubes on murine embryonicstem cells

Abstract: Stem cells nanotechnology has emerged as a new exciting area, and holds great potential for research and development of stem cells as novel therapeutic platforms for genetic, traumatic, and degenerative medicine. Vital to the success of this technology are approaches that reproducibly facilitate in vivo cell tracking, expansion, differentiation, and transplantation. Herein we reported the effects of CdSe/ZnS quantum dots covered multi-walled carbon nanotubes (FMNTs) on mice embryonic stem cell line CCE cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…Using a peptide nanofiber scaffold, a group of researchers succeeded in synthesizing 18 different peptides with mouse neural stem cells . A similar approach was adopted to study cartilage repair with an electrospun, porous 3D nanofiber scaffold . Nanofibrous structured scaffolds has been shown to favorably support bone tissue (osteoblast, osteoclast, and fibroblast) proliferation and differentiation in 3D cell cultures for possible implantation .…”
Section: D Nanoscaffold Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a peptide nanofiber scaffold, a group of researchers succeeded in synthesizing 18 different peptides with mouse neural stem cells . A similar approach was adopted to study cartilage repair with an electrospun, porous 3D nanofiber scaffold . Nanofibrous structured scaffolds has been shown to favorably support bone tissue (osteoblast, osteoclast, and fibroblast) proliferation and differentiation in 3D cell cultures for possible implantation .…”
Section: D Nanoscaffold Developmentmentioning
confidence: 99%
“…11 A similar approach was adopted to study cartilage repair with an electrospun, porous 3D nanofiber scaffold. 51 Nanofibrous structured scaffolds has been shown to favorably support bone tissue (osteoblast, osteoclast, and fibroblast) proliferation and differentiation in 3D cell cultures for possible implantation. 52,53 In a recent report on breast cancer, it was revealed that a 3D nanofiber scaffold exerted significant influence on CD44+/CD24− by limiting their migration and invasion tendencies thus further highlighting the importance of cell-extracellular matrix interaction in stem cell proliferation, which could be exploited for designing therapeutic interventions with better efficacies.…”
Section: Developmentmentioning
confidence: 99%
“…An MTT (tetrazolium salt) assay was conducted to evaluate the effects of dMNTs on ES CCE cells. The inhibition curve of cell proliferation can be drawn [27,28].…”
Section: Es Cells' Culture and Mtt Analysismentioning
confidence: 99%
“…In addition, the broad emission spectrum of the donor, with its long red tail, can often overlap significantly with the emission spectrum of the acceptor. Several recent reports have confirmed that luminescent semiconductor quantum dots (QDs), such as CdSe and CdTe, are able to participate in resonance energy transfer processes analogous to FRET [7][8][9][10][11][12], which makes these materials good candidates to overcome some of the limitations associated with conventional organic dye molecules in FRET-based studies of biomolecular structure, ligandreceptor binding, etc.…”
Section: Introductionmentioning
confidence: 97%